-3(-4a - 2) = 12a + 6
-3(-4a - 2)
=> multiply -3 by everything in the parenthesis
-3 * -4a = 12a
-3 * -2 = 6
=> combine like terms
12a + 6
Copyright © 2021.
New to disilab? Create
Login with your social network
Your password must be at least 6 characters long and must contain
letters, numbers and special characters. Cannot contain whitespace.
Already on disilab? Log
Create account with your social network
Enter your username or email to reset your password.
You will receive an email with instructions on how to reset your password. If you are experiencing
resetting your password contact us or
send us an email
Not a member? Create